Wells Cathedral
At Lincoln and elsewhere, arcading had been used two-dimensionally to secure unity over a large area. Wells breaks new ground, in that there is a third dimension involved. The massive wall is dissolved by piercing and folding in a remarkable manner, calling for the highest skills of execution and overall control. The complete work was painted and gilded, and the lancet windows, intended for stained glass, were completely integrated in the scheme.